2003
DOI: 10.1088/0022-3727/36/5/320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air annealing on opto-electrical properties of amorphous tin oxide films

Abstract: Amorphous tin oxide films, 100-800 nm thick and of resistivity ∼6-8 m cm, were deposited on glass substrates using a filtered vacuum arc with an oxygen background gas pressure of 4.0 mTorr. The films were annealed in air at a temperature of 300˚C for 1, 3, 5, 7, and 10 min. Film morphology, structure, composition, roughness, and light transmission were determined before and after the annealing, on cold samples, with atomic force microscopy, x-ray diffraction diagnostics, x-ray photoelectron spectroscopy, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…However at higher temperatures, the surface mobility of constituent elements increases, and the growth of face grains are preferred. The atomic force microscope images undoped SnO 2 are compared with the published results [17,25,[33][34][35][36][37][38]. It is observed that the crystallization processes in undoped SnO 2 with increasing substrate temperature followed similar character, which is shown by XRD analysis, also the degree of surface roughness increases.…”
Section: Discussionmentioning
confidence: 82%
“…However at higher temperatures, the surface mobility of constituent elements increases, and the growth of face grains are preferred. The atomic force microscope images undoped SnO 2 are compared with the published results [17,25,[33][34][35][36][37][38]. It is observed that the crystallization processes in undoped SnO 2 with increasing substrate temperature followed similar character, which is shown by XRD analysis, also the degree of surface roughness increases.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, SnO 2 thin films could be deposited with FVAD system on low temperature substrates, such as polymers that could not sustain temperatures above 80°C [16]. The dependence of the structure, composition, and electrical properties of room temperature FVA deposited SnO 2 thin films on the oxygen background pressure (0.42-1.06 Pa), and film thickness (100-800 nm) were reported by Ben-Shalom et al [11], Kaplan et al [12], Alterkop et al [14] and Parkansky et al [15]. All deposited films were amorphous, with the lowest electrical resistivity of 3-5 · 10 À4 X cm, obtained by rapid thermal annealing (RTA) [11,12].…”
Section: Introductionmentioning
confidence: 89%
“…SnO (TCO) films that contain In or Cd, as they are less expensive and non-toxic. Doped or undoped SnO 2 thin films were prepared by spray pyrolysis [5], reactive electron beam evaporation [6], rf magnetron sputtering [7,8], chemical vapour deposition (CVD) [9], reactive ion assisted deposition [10] and filtered vacuum arc deposition (FVAD) [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…One can observe that the optical transmittance decreases as the annealing temperature increases. This may be due to to the structural transformation of the films during annealing [26,27]. It can also be seen that the fundamental absorption edge shifts to higher wavelength with increasing the annealing temperature.…”
Section: Optical Analysis 321 Absorption Coefficientmentioning
confidence: 99%
“…5, α increases with increasing both the photon energy and annealing temperature. This behavior could be due to the size effect [27]. Depending on the value of α, its spectral distribution can be categorized as high absorption or exponential edge region.…”
Section: Optical Analysis 321 Absorption Coefficientmentioning
confidence: 99%